0
$\begingroup$

I tried to follow Jann Goschenhofer's answer here, but I don't understand

  1. How $x_i^T$ in $Criterion_{Ridge} = \sum_{i=1}^{n}(y_i-x_i^T\beta)^2 + \lambda \sum_{j=1}^p\beta_j^2$ became just $X$ without transpose in $Criterion_{Ridge} = (y-X\beta)^T(y-X\beta) + \lambda\beta^T\beta$
  2. How did he just replace $y^TX\beta$ with $\beta^TX^Ty$ in the break down of the $Criterion_{Ridge}$? He wrote $ = y^Ty - \beta^TX^Ty - y^TX\beta+ \beta^Tx^TX\beta + \lambda\beta^T\beta$ is equal to $ = y^Ty - \beta^TX^Ty - \beta^TX^Ty + \beta^TX^TX\beta + \beta^T\lambda I\beta$ ? If he just used the fact that $(AB)^T=B^TA^T$ then he should have written $(\beta^TX^Ty)^T$ and not just $\beta^TX^Ty$
$\endgroup$
  • 1
    $\begingroup$ For numbers (considered as $1\times 1$ matrices) $x$, it is obvious that $x^\prime=x.$ This relation is exploited repeatedly in the algebra. $\endgroup$ – whuber Jun 18 '18 at 18:44
  • $\begingroup$ @whuber, can you please explain in more details? Also, what about my second question? $\endgroup$ – theateist Jun 18 '18 at 20:29
1
$\begingroup$

How did he just replace $y^T X \beta$ with $\beta^TX^Ty$

As @Whuber points out - the trick is to see that the two terms you are referring to are actually scalar (not vectors) and so transposing them has no effect as $x^T = x$ for scalar $x$.

You can see these are scalar from their dimensions:

Let $m$ be the number of observations and $n$ be the number of features

  • $y: m \times 1$
  • $\beta: n \times 1$
  • $X: m \times n$
  • $y^T X \beta: (1 \times m) \ (m \times n) \ (n \times 1) = 1 \times 1$
  • $\beta^T X^T y: (1 \times n) \ (n \times m) \ (m \times 1) = 1 \times 1 $

Use vector transpose properties to see they are the same:

  • $(y^T X \beta)^T = \beta^T X^T y^{TT} = \beta^T X^T y $
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.